QUALITY OF MOVING SERVICES THROUGH THE PLAVON APPLICATION AT THE POPUBLATION AND CIVIL REGISTRATION SERVICE OF SIDOARJO REGENCY - Rizqiyah, Nadya; Mursyidah, Lailul (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the quality of outbound transfer services through the Online Service (PLAVON) application developed by the Sidoarjo Regency Population and Civil Registration Office as an e-government innovation to enhance efficiency and accessibility in population administration. Method: A qualitative descriptive approach was employed, guided by the SERVQUAL framework encompassing tangibles, reliability, responsiveness, assurance, and empathy. Results: Findings reveal that PLAVON effectively expedites document processing, reduces face-to-face queues, and improves service accessibility. Nevertheless, challenges persist in the form of technical disruptions, low digital literacy among the community, and limited human resources. In response, the Office implemented mitigation strategies such as offline service alternatives, digital literacy education, and collaboration with higher education institutions to strengthen capacity. Novelty: This study contributes by integrating SERVQUAL analysis into the assessment of a local e-government innovation in Indonesia, highlighting both the potential and limitations of PLAVON as a model for enhancing digital public services in regions facing infrastructural and literacy constraints.